Avaliação do comportamento e bem-estar do peixe-boi-da-Amazônia (Trichechus inunguis NATTERER, 1883) juvenil em cativeiro - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
This paper aims to observe and describe the behavior of juvenile manatees in captivity and measures the degree of animal welfare for the first time in the species. Agonist behaviors and stereotypy in captivity were emphasized. In order to increase the behavioral knowledge of the species and produce data on undesirable behaviors, helping to measure animal welfare. Trichechus inunguis is the largest and most endangered aquatic mammal in the Amazonian river waters, which was severely collapsed in the 1930s to 1950s and caused its population to fall dramatically. vessel flow, changes in dam and dam courses and the same protected by law is still consuming their meat.. The study took place between May and July 2019, at the zoo of the University of Amazonia (UNAMA) located in the city of Santarém-PA, using 9 juvenile animals. Regarding the methodology for behaviors, the sampling method ―Ad libitum‖ was recorded for the making of the etogram. For the etological records, the technique used was ―scan‖ with the aid of camera recordings and annotations in spreadsheets differentiated by the categories: affiliate, agonist, food, stereotype, interspecific and individual. More frequent records were obtained of individual behavior (36%) regarding undesirable agonist (5%) and stereotyped (3%) behaviors. Regarding the BEA measurement, protocols were adapted analyzing: health indicator, nutritional indicator, behavioral indicator and environmental indicator, considering the following categories: Inadequate (1), Adequate (3) and Regular (2). The median, minimum and maximum were obtained: nutritional 2 (2,2), health 2 (2,1), environmental 1 (1,1) and behavioral 2 (3,1). The protocol proved to be an important tool for the diagnosis of BEA, helping the teams that rehabilitate these animals, also signaling the critical points, highlighting the scenario quantitatively and qualitatively.
Keywords: Sirênio; Protocolo; Etograma